Oor Calvyn se siening van die nagmaal - Smit, DJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2014)
Calvin’s views on the Lord’s Supper During the Calvin commemoration of 2009, the question was often asked whether his views on the Lord’s Supper still hold ecumenical potential for today. A first section deals with the controversial question where exactly Calvin’s views on the Lord’s Supper should be found and how it should be described. In an attempt to respond to this question still challenging contemporary scholarship, a second section attempts to provide an answer in terms of Calvin’s comprehensive understanding of the presence of Christ. His views regarding the Supper can only be construed as integral part of his views regarding Christ’s presence. Five forms of Christ’s presence are distinguished in Calvin’s thought, namely a living presence, a spiritual presence, a sacramental presence, a eucharistic presence and an ecclesiological presence. A final section considers the contemporary ecumenical question whether these views could be appropriated today, in the light of several serious obstacles.